PP.11.07: PRIMARY HYPERTENSION AND NEPHROSCLEROSIS. NEPHROSCLEROSIS BEGINS FIRST WITHIN THE LEFT KIDNEY AND THIS SIGN COULD BE CALLED AS ERGUN SIGN. (June 2015) - Ergun, Y.; Sagliker, H.S.; Sagliker, Y.; Aikimbaey, K.; Firinciogullari, H.; Yildiz, I.; Paylar, N.
Abstract : Objective: Since 1995 a sign noticed by Ergün in which echo pattern of some patients showing differences and left kidney echo pattern was hyperechogenic as compared to right side. Changes were hyperechogenic, somewhat like thick corn or large sand particules and kidney had some pathological changes on parenchima pyelon ratios and borders. Figure. No caption available. Design and method: Baselines performed in Nephrology Clinics then patients seen for abdominal ultrasonography and color doppler ultrasonography performed by radiologists blindly without being informed. Angles of both renal arteries arising from abdominal aorta., lumen diameters of renal arteries and blood flows and outputs performed..51 patients enrolled to study. Results: Totally 51 patients, 28 were females, mean average of ages were 53.6 years, 23 males with the average of age 54.5. Hypertension clasifications were class II and III according to ISH . The small kidney was present in 11 rights and 15 left kidneys. Parenchima/pyelon border irregularities were present in 12 right and 42 left kidneys. Pathological abnormalities were in 22 right and 29 left kidneys. Renal arteries diameters were similar(5 mm). The flow in right renal arteries were 434 ml/min., but 393 ml/min. in lefts. Narrow angle was 13 in right side and 24 in left kidneys. The increase in ecogenity was 14 in right but was 45 in left kidneys. Nephrosclerosis was 27.45% in right kidney but 88.23 in lefts. VMA values were normal in patients. Conclusions: Results emphysized nephrosclerosis in primary hypertension start initially in left kidney and nephrosclerosis level is one or two points greater than right kidney. This sign in primary hypertension could be named Ergun Sign.